TECHNOLOGICAL INNOVATIONS AS A KEY FACTOR OF COMPETITIVENESS IN THE GLOBAL MARKET - OSTAPCHUK, Olha; MYKOLAICHUK, Vasyl (Herald of Khmelnytskyi National University. Economic sciences, 2024)
Technological innovations today are becoming not just a key, but an essential success factor for modern enterprises on the global market. The level of competitiveness today is determined not only by the quality of products or services, but also by the speed of their implementation, adaptability to changes and improvement of processes.The article is aimed at studying the role of technological innovations in enhancing the competitiveness of enterprises in the global market. The study found that the introduction of advanced technologies, such as the Internet of Things, artificial intelligence, cloud technologies, etc., plays a significant role in improving the efficiency of modern enterprises and ensuring the competitiveness of enterprises. The article also analyzes the impact and benefits of technological innovations for entrepreneurship, including production, logistics, marketing, and customer service. It was found that such innovations help companies reduce costs, improve the quality of products and services, and accelerate the development of new products and markets. In addition, the key factors of success in the implementation of technological innovations, such as openness to change, flexibility in solving problems, and the ability to respond quickly to market and technological trends, are highlighted. The author summarizes that innovative activities allow enterprises not only to strengthen their positions in existing markets, but also to create new opportunities for the development of a new digital environment. The author analyzes the current state and prospects for the development of technological innovations in Ukraine, in particular, in the context of Industry 4.0 and technoglobalization. The study showed that Ukraine has the potential to develop technological innovations, particularly in the field of information technology, but needs additional funding and integration into the global scientific space.
Keywords: labor potential; labor resources; social capital; migration; unemployment; European integration